2023
DOI: 10.1039/d3ra06293g
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gardenia seeds-based carbon dots for bacterial imaging and antioxidant activity in aqueous and oil samples

Hung-Wen Tsai,
Tsunghsueh Wu,
Chiu-Lan Hsieh
et al.

Abstract: Gardenia seed carbon dots: bacterial imaging and antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…In this mechanism, the CQDs might bind to cell surface receptors first before they can be transported into the cell. 10 As depicted in Figure 2 A, bacteria without CQDs did not exhibit any PL emission, while bacteria with CQDs showed clear PL signal uniformly throughout the cells, confirming the facile passage of CQDs through the cell membranes and their subsequent uptake by the cells. These observations strongly suggest the accumulation of the synthesized CQDs in both the cell membranes and cytoplasm.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…In this mechanism, the CQDs might bind to cell surface receptors first before they can be transported into the cell. 10 As depicted in Figure 2 A, bacteria without CQDs did not exhibit any PL emission, while bacteria with CQDs showed clear PL signal uniformly throughout the cells, confirming the facile passage of CQDs through the cell membranes and their subsequent uptake by the cells. These observations strongly suggest the accumulation of the synthesized CQDs in both the cell membranes and cytoplasm.…”
Section: Resultsmentioning
confidence: 74%
“… 9 In recent years, studies have identified gardenia seeds as a viable carbon source for synthesizing CQDs. 10 , 11 The gardenia seeds are rich in functional groups on their surface, and deriving CQDs from plant seeds aligns with the principles of waste utilization, offering a sustainable, environmentally friendly, low-toxicity, and green synthesis approach for CQDs. 12 , 13 However, some drawbacks exist in these methods such as stringent synthesis conditions and relatively long reaction times.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations